ANALYSES OF CONCOMITANT BONE FRACTURES IN MILITARY PERSONNELWITHLIMBAMPUTATIONS IN THE AREA OF THE ANTITERRORIST OPERATION INEAST UKRAINE - Buryanov, A.A.; Bespalenko, A.A.; Tsema, Ie.V.; Dinets, A.V. (The Ukrainian Scientific Medical Youth Journal, 2017)
The aim – to investigate and evaluate bone fractures in military personnel with limb amputations due to participation in the anti-terrorist operation (ATO) in the East Ukraine. Patients and methods. All military personnel of the Armed Forces was included into study. Patients were identified with limb amputations in the period from 01.06.2014 to 30.06.2016 in the ATO zone, and were treated in medical institutions of the Ministry of Defense of Ukraine. Among 7091 patients with injuries in ATO, 152 patients with limb amputations were identified. Results and discussion. Out of 152 patients, 47 (31%) patients with limb amputations were also diagnosed with bone fractures, whereas in 107 (69%) patients amputations were not associated with bone fractures. The military rank of the cohort did not demonstrate significant difference. Ana- lyses of the level of amputation of the lower limbs showed femoral middle 1/3 in the group of patients with amputations and bone fractures in 6 (17%) patients, which is significantly more frequentas compared to the group of patients with amputations without concomitant fractures of bones – 3 (4 %) of patients (p = 0.023). Amputation of the foot in a group of patients with amputations and bone fractures was diagnosed in 2 (6%) patients, which is 4.5 times less often, as compared to 20 (27%) patients in the group of patients with amputations without concomitant bone fractures (p = 0.023). Linear regression showed a significant association of bone fractures and amputations of the foot (p = 0.012); which indicated the severity of the combined trauma in the cohort. Multiple logistic regression showed aOR 0.171 (95% CI 0.04-0.8), indicating a significant low probability of bone fractures during foot amputation (p = 0.022). Conclusions. The results of this study of wounded patients in a hybrid war indicated that bone fractures are more often associated with amputations at the level of the femoral middle 1/3, but are less often diagnosed in patients with foot amputations. Bone fractures are not associated with the frequency of reamputation. Patients injured in the ATO zone in the East Ukraine demonstrated different clinical features as compared to other armed conflicts, and associated with amputations and other severe injuries.